2020
DOI: 10.1007/s41042-020-00026-8
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of Effects of Cooperative Learning on Prosocial Behavior in Middle School

Abstract: In this study, we tested the effects of cooperative learning on students' prosocial behavior. Cooperative learning is a small-group instructional technique that establishes positive interdependence among students and, unlike most current school-based programs, does not mandate a formal curriculum. Given the emphasis in cooperative learning on peer reinforcement for positive and helpful behavior during learning activities, we hypothesized that cooperative learning would promote higher levels of prosocial behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 50 publications
1
46
0
6
Order By: Relevance
“… Leslie et al (2016) describe sixteen family interventions that have been shown to prevent most of the common and costly psychological and behavioral problems. In schools, interventions such as PeaceBuilders ( Embry, Flannery, Vazsonyi, Powell, & Atha, 1996 ), the Good Behavior Game ( Embry, 2002 ; Kellam et al, 2011 , Kellam et al, 2012 ), Positive Action ( Flay & Allred, 2003 ), and cooperative learning ( Roseth, Johnson, & Johnson, 2008 ; Van Ryzin & Roseth, 2019 ; Van Ryzin, Roseth, & Biglan, 2020 ) result in reductions in “fast life” strategies and higher student investments in education, work, and positive lifestyles. This is especially true for the children exposed to the highest levels of neighborhood violence and victimization ( Vazsonyi, Belliston, & Flannery, 2004 ).…”
Section: The Nurture Consiliencementioning
confidence: 99%
See 1 more Smart Citation
“… Leslie et al (2016) describe sixteen family interventions that have been shown to prevent most of the common and costly psychological and behavioral problems. In schools, interventions such as PeaceBuilders ( Embry, Flannery, Vazsonyi, Powell, & Atha, 1996 ), the Good Behavior Game ( Embry, 2002 ; Kellam et al, 2011 , Kellam et al, 2012 ), Positive Action ( Flay & Allred, 2003 ), and cooperative learning ( Roseth, Johnson, & Johnson, 2008 ; Van Ryzin & Roseth, 2019 ; Van Ryzin, Roseth, & Biglan, 2020 ) result in reductions in “fast life” strategies and higher student investments in education, work, and positive lifestyles. This is especially true for the children exposed to the highest levels of neighborhood violence and victimization ( Vazsonyi, Belliston, & Flannery, 2004 ).…”
Section: The Nurture Consiliencementioning
confidence: 99%
“…As prevention science has accumulated a large array of tested and effective interventions, the field has increasingly turned to the question of how those interventions could be so widely applied that they affect entire populations. Examples of these efforts include (a) the implementation of the PAX Good Behavior Game in more than 40,000 elementary school classrooms worldwide, which grew out of the studies by Sheppard Kellam and colleagues ( Kellam et al, 2012 ), which showed the long term benefit of the Good Behavior Game; (b) the efforts of Wilson, Atkins, and Hayes to disseminate the Ostrom Principles ( Wilson, Ostrom, & Cox, 2013 ) by integrating behavior change techniques from clinical psychology ( Polk & Schoendorff, 2014 ), to help small groups function more effectively ( Atkins, Wilson, & Hayes, 2019 ); (c) the extensive work that is being done to disseminate clinical interventions derived from Acceptance and Commitment Therapy ( Hayes et al, 2016 ) that focus on promoting psychological flexibility ( Brown, Glendenning, Hoon, & John, 2016 ; Hayes, 2019 ; Tol et al, 2020 ); and (d) our own efforts to increase the prevalence of nurturing environments by enhancing the developmental contexts of children and youth ( Biglan, 2020a ; Biglan, Van Ryzin, Moore, et al, 2019 ; Biglan, Van Ryzin, & Westling, 2019 ; Van Ryzin et al, 2020 ; Van Ryzin, Roseth, Fosco, Lee, & Chen, 2016 ).…”
Section: Scaling Up and Scaling Outmentioning
confidence: 99%
“…These positive relationships can interrupt the process of deviant peer clustering and, in turn, reduce substance use (Van Ryzin & Roseth, 2018a, 2018b, 2019a. Cooperative learning can also significantly reduce bullying, victimization, stress, and emotional problems, and enhance prosocial behavior and social-emotional skills (Van Ryzin & Roseth, 2018c, 2019b). Finally, cooperative learning has demonstrated robust positive effects on academic engagement and achievement (see meta-analyses by Johnson & Johnson, 1989Roseth et al, 2008).…”
Section: School-based Interventionsmentioning
confidence: 99%
“…Cooperative learning can generate significant reductions in bullying and victimization, with effect sizes ranging from .37 to .69 (Van Ryzin & Roseth, 2018a), mediated by improvements in peer relations and affective empathy (Van Ryzin & Roseth, in press). Cooperative learning has also been found to reduce alcohol and tobacco use (Van Ryzin & Roseth, 2018b) and to promote prosocial behavior (Van Ryzin & Roseth, 2019). These findings suggest that cooperative learning can promote substantial increases in academic achievement while simultaneously addressing some of the social processes that can promote aggressive and antisocial behavior.…”
Section: Prevention Approaches Targeting Aggressive Behaviormentioning
confidence: 99%